A10.02 Deficiency in IL-1 receptor type 2 aggravates K/BXN serum transfer-induced arthritis in mice, but has no effect in endotoxemia. (24th February 2016) - Martin, P; Palmer, G; Rodriguez, E; Seemayer, CA; Talabot-Ayer, D; Gabay, C
Abstract : Introduction: The biological activity of interleukin (IL)-1 is tightly regulated by a specific receptor antagonist (IL-1Ra) and the decoy receptor IL-1R2. The role of IL-1Ra has been well demonstrated in IL-1Ra deficient mice. In contrast, the role of endogenous IL-1R2 remains widely unknown. Methods: We generated IL-1R2 deficient mice in a C57BL/6 background and investigated the role of IL-1R2 in both lipopolysaccharide (LPS)-induced lethality by injecting 10 mg/kg E. coli LPS intraperitoneally (i.p.), and in systemic inflammatory responses induced by i.p. injections of 10 µg/kg IL-1β. Lethality was monitored daily and serum cytokine levels were measured at different time points by ELISA, respectively. Arthritis was induced by injecting i.p. 1.5 mg purified arthritogenic IgGs purified from K/BxN serum. Arthritis severity was assessed by clinical and histological scoring. Tissue mRNA levels of cytokines were measured by real-time PCR. Results: IL-1R2 deficient mice bred normally and exhibited a grossly normal phenotype. IL-1R2 was selectively expressed by wild-type (WT), but not IL-1R2 deficient, neutrophils. The number of immune cells in bone marrow, spleen and peripheral blood was similar in IL-1R2 deficient and WT mice. The phagocytic function and oxidative burst of IL-1R2 deficient neutrophils were normal. The rate of LPS-induced mortality and the level of inflammatory responses to IL-1b were similar in IL-1R2 deficient mice and their WT littermates. In contrast, IL-1R2 deficiency was associated with aggravated arthritis severity. Levels of IL-6, IL-1β, CXCL-1 and CXCL-2 mRNA were significantly increased in ankles of IL-1R2 deficient mice. Immunohistochemical analyses indicated that IL-1R2 is mainly expressed by infiltrating neutrophils. Conclusions: These data show that the decoy receptor IL-1R2 plays an important role during K/BxN serum transfer-induced inflammatory arthritis and suggest that neutrophils exert anti-inflammatory activities in arthritis by expressing IL-1R2. However, in contrast to IL-1Ra, IL-1R2 is not essential for normal homeostasis and systemic responses to LPS and acute IL-1 administration.